A first look at the effects of long inter‐pregnancy interval and advanced maternal age on perinatal outcomes: A retrospective cohort study. Issue 3 (19th April 2017) - Qin, Chunxiang; Mi, Chunmei; Xia, Aibin; Chen, Wei‐Ti; Chen, Chunxia; Li, Ying; Li, Yao; Bai, Wenhui; Tang, Siyuan
Abstract: Background: After China's One‐child Policy was replaced with the Two‐child Policy in 2013, the rate of second pregnancies with a longer inter‐pregnancy interval (IPI) has suddenly increased in that country; however, the effect of long IPIs (≥49 months) on perinatal outcomes remains unreported. Methods: This was a retrospective cohort study in China from July 2015 through June 2016. We used univariate and multivariate logistic regression models to test the associations among IPI, maternal age, and perinatal outcome (preterm delivery, term low birthweight, and small‐for‐gestational age). We included baseline factors and variables with biological plausibility as confounders. Results: Our analytic sample included 3309 second pregnancies. The mean IPI was 75.36 months. Compared with second pregnancies with a short IPI of 7‐24 months, those with long IPIs had higher adjusted odds ratios (ORs) of preterm delivery (1.70‐2.00 [95% CI 1.20‐3.33]) and term low birthweight (2.16‐2.68 [1.10‐6.17]), but not small‐for‐gestational age. The mean maternal age at current delivery was 32.0 years. Compared with the reference group (25‐29 years), second pregnancies for the oldest maternal age group (≥35 years) showed no statistically significant increased ORs for adverse perinatal outcomes. Conclusion: Long IPI is a significant contributor to preterm delivery and term low birthweight. Health care providers need to pay close attention to preterm delivery prevention and fetal growth during prenatal care for second pregnancies where the mothers have long IPIs.